Factors Influencing Consumer-Perceived Risk in E-Commerce Transactions in China - Zheng, Anqi (2012)
Over the last decade, electronic commerce has become one of the fastest growing markets in China and it is still growing at a dramatic speed. E-commerce introduces a convenient way for consumers to do shopping. During the online transaction processes, different types of risks are perceived by consumers due to the uncontrollable aspects of the Internet. The facets of perceived risk include social risk, financial risk, performance risk, psychological risk, privacy risk and time risk. This research examines the factors influencing consumer’s risk perception of online transactions, with a focus on trust, novelty and dread. The research model is the psychometric paradigm.